Experimental investigation on blast and post-blast performance of reinforced concrete straight-wall arches strengthened with polyurea coating. (3rd July 2023) - Song, Dianyi; Tan, Qinghua; Cao, Y.Y.Y.; Hu, Yufeng
Highlights: Blast resistance of RC straight-wall arch is investigated by contact explosion experiments. Damage modes on the front blast surface include cratering and punching; those on the back blast surface include punching, collapsing and bulging. Polyurea coating with sufficient thickness can significantly improve the blast resistance of the arch. Higher concrete strength reduces the damage area, but its influence on the depth of the damaged region is unclear. Abstract: Reinforced concrete (RC) straight-wall arches are commonly used in underground construction because of their superior load-bearing capacity. During their life cycle, RC straight-wall arches are at risk of explosion in military attacks, terrorist activities and traffic accidents, making it important to study and improve their blast resistance. In this study, contact explosion tests are conducted on five RC straight-wall arches, and the effects of concrete strength, charge location, and thickness of polyurea coating are discussed. After the explosion tests, the damaged arches are repaired with a concrete repair adhesive and the residual load-carrying capacity are then tested. The results show that increasing the concrete strength from C50 to C70 leads to a 25% smaller punching hole on the front blast surface. Moreover, the polyurea coating sprayed on the inner surfaces of the RC straight-wall arches can significantly improve the blast resistance of the RC straight-wall arches. For instance, specimen A3 (C50, with 5 layers of coating) has a 38% reduction in the depth of the damaged region on the back blast surface compared to specimen A4 (C70, without polyurea coating), in spite of the higher strength of specimen A4. Additionally, the study reveals that the concrete repair adhesive offers a good repair effect on the damaged arches and its application will not negatively affect the vertical load-bearing capacity of the arches.